IMPLEMENTASI SISTEM PENGUPAHAN DALAM PERSPEKTIF HUKUM KETENAGAKERJAAN PADA PERUSAHAAN - Lily Chairunnisa; Zahra Azizah (Jurnal Riset Multidisiplin Edukasi, 2026)
The wage system is an important aspect of the employment relationship between workers and employers. Wages are not only a source of livelihood for workers but also a form of appreciation for the labor and contributions given in the work process. In practice, the implementation of wage systems in companies often raises various issues, such as non-compliance with minimum wage regulations, delays in wage payments, and a lack of transparency in determining wage structures and scales. This study aims to analyze the implementation of wage systems in companies and examine their compliance with labor law regulations in Indonesia. The research method used is normative legal research with statutory and conceptual approaches. The data sources consist of primary, secondary, and tertiary legal materials obtained through library research. The results show that the wage system in companies has generally been regulated clearly in legislation, particularly in labor laws and related regulations. However, in practice, there are still several obstacles in its implementation that may lead to industrial relations disputes. Therefore, companies are required to comply with labor law provisions, and effective government supervision is needed to ensure the fulfillment of workers' rights and the creation of harmonious industrial relations.